2010
DOI: 10.1118/1.3302141
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deformable image registration accuracy using computational modeling

Abstract: Computer aided modeling of anatomic deformation, allowing various techniques and protocols in radiation therapy to be systematically verified and studied, has become increasingly attractive. In this study the potential issues in deformable image registration ͑DIR͒ were analyzed based on two numerical phantoms: One, a synthesized, low intensity gradient prostate image, and the other a lung patient's CT image data set. Each phantom was modeled with region-specific material parameters with its deformation solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
121
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 39 publications
2
121
0
1
Order By: Relevance
“…In a comprehensive publication, Kashani et al (31) reported interalgorithm comparison at different institutions and noted that “no algorithm was uniformly accurate across all regions in a phantom”, with larger errors seen in regions of significant shape changes and in areas of uniform contrast. As noted by Zhong et al, (45) performance in regions with low‐intensity gradients is difficult to assess. This study highlights the need for a direct measure derived from the displacement field when assessing accuracy of deformable warping for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a comprehensive publication, Kashani et al (31) reported interalgorithm comparison at different institutions and noted that “no algorithm was uniformly accurate across all regions in a phantom”, with larger errors seen in regions of significant shape changes and in areas of uniform contrast. As noted by Zhong et al, (45) performance in regions with low‐intensity gradients is difficult to assess. This study highlights the need for a direct measure derived from the displacement field when assessing accuracy of deformable warping for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that registration errors are prone to emerge in regions with uniform image intensity and low‐intensity gradient regions and are not visible with standard voxel‐based methods (45) . Although it is hard to identify differences by inspecting the images directly, analysis of the deformation field through the CURL operator provides complementary information that better identifies and characterizes tissue warping.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations